COMPETENCE OF PRIMARY SCHOOL SCIENCE TEACHERS IN TEACHING SCIENCE SUBJECTS: THE CASE OF PRIMARY SCHOOLS IN NORTH SHEWA ZONE, AMHARA REGION - ETHIOPIA (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2021)
Primary school science teachers’ competencies were analyzed in this paper. The importance of science teachers’ competencies in teaching science is underlined and also the existing primary school science teachers’ competency of subject matter knowledge (SMK);methodology; laboratory utilization; planning of lesson and implementation of the plan and competency of formative continuous assessment were studied. While schools were selected using purposive sampling, the data sources were selected through random sampling techniques. Data was collected through close-ended and open-ended questionnaires, focused group discussion, classroom observation with rating scale and  semi-structured interview. The data were analyzed by statistical analysis using chi-square, one way ANOVA, f-test, and Tukey’s HSD test. The result of the research revealed that primary school science teachers in the sample schools were found less competent in all the areas. They lack fundamental competence in some areas under investigation. Based on this some recommendations were forwarded.
Keywords: competencies; pedagogical content knowledge; pedagogical knowledge; science teacher; subject matter knowledge